Development of interactive multimedia courseware within collaborative learning environment for computer network education / Nurul Hidayah Ahmad Alemi - Ahmad Alemi, Nurul Hidayah (2015)
The development skill to produce a well-trained and competent vocational and technical trainee is the aim for Kolej Komuniti Masjid Tanah. As to enrich the learning process and provide a discussion medium to students, the lecturers are expected to be creative and innovative to integrate the ICT approaches in teaching and learning. The aim of this research is to develop Computer Network Education Courseware for Computer Network subject within collaborative learning environment called CNEC in the Moodle Learning Management System (LMS) together with Collaborative Tools in Moodle which is Forum. The methodology of this research was based on the Instructional Design Model (ADDIE). The courseware was developed in Bahasa Melayu and SCORM compliant environment. It is made up of 9 learning modules: Pengenalan, Objektif Pembelajaran, Pengenalan kepada Rangkaian, Pengalamatan Rangkaian, Pengiraan Alamat Rangkaian, Rekabentuk Rangkaian, Kuiz, Rumusan and Rujukan. In order to test whether the courseware is suitable in terms of usability, try-out was done to a sample of 25 semester 1 students that enrolled Computer Network subject. The respondent strongly agree by the percentage of 36% to 68% and 28% to 40% agree that the CNEC courseware is acceptable to use for real usability in learning of Computer Network subjects. Therefore, the results from the try-out received positive feedback which signifies the courseware is considered acceptable for effectiveness study. As for further improvement of the CNEC courseware need the evaluation for the effectiveness, efficiency, learnability through appropriate case study among the lecturers and students from Community College in Malaysia.